Neuroleptic dosage for asian patients - Ismail, Rusli
The aim of this study is to determine the therapeutic dose and the optimum plasma level of chlorpromazine for treatment of acute schizophrenia. Fifty-four patients diagnosed as schizophrenia and schizophreniform disorder ( DSM - I IIR ) admitted to the ·' psychiatric ward in a teaching hospital in Malaysia were selected for the study.The treatment was started with 300 mg of chlorpromazine daily and the dose was increased forthnightly til l they improved. The clinical improvement was assessed by BPRS and the chlorpromazine plasma level was measured by HPLC method.It was found that the most frequently prescribed dose was 500 mg perday., 300 mg being the lowest and 900 mg the highest ; the mean plasma concentration of chlorpromazine was 67 . 9 ngj ml.There was a poor correlation between chlorpromazine dose and plasma level. I t is concluded that majority of the acute schizophrenia requi red a moderate dose of chlorpromaz i ne and the plasma concentration of 67 . 9 ng/ ml is within the therapeutic range.